Respuesta :

Answer:

Step-by-step explanation:

The given expression has the first term n=1, so exponent = n-1 = 0

Similarly, for the second term n = 2, n-1 = 1

These exponents eliminate options 2 and 4.

Furthermore, the base is a fraction of 1/2, which applies to options 1 and 2 only.

The only viable option left that satisfies all conditions is option 1, which has exponents 0 and 1, with a base of (1/2).

The second partial sum for [tex]\sum\limit^\infty_{n=1}\; 3* (\frac{1}{2})^{n-1}[/tex] is [tex]3* (\frac{1}{2})^0 + 3* (\frac{1}{2})^1[/tex]

The correct option is (1)

What is Summation ?

A summation, also called a sum, is the result of arithmetically adding numbers or quantities. A summation always contains a whole number of terms.

The given summation is:

[tex]\sum\limit^\infty_{n=1}\; 3* (\frac{1}{2})^{n-1}[/tex]

If we put two values of n i.e., n=1,2. hen we get the following summation series

=[tex]3* (\frac{1}{2})^{1-1} + 3* (\frac{1}{2})^{2-1}[/tex]

=[tex]3* (\frac{1}{2})^0 + 3* (\frac{1}{2})^1[/tex]

The option answer matches with the option 1.

Hence the correct option is (1)

Learn more about summation here:

https://brainly.com/question/17104120

#SPJ2